Non-verbal agents of theatrical retranslation: Women’s identity and the Spanish classics - Jorge Braga Riera (JoSTrans: The Journal of Specialised Translation)
Despite the burgeoning interest in literary retranslation, there is still a need to investigate how linguistic, contextual, and personal factors influence the translation of a previously translated (and performed) play into a given target language and culture. This article aims to illuminate the extralinguistic agents (personal, social, performative, paratextual) that specifically intervene in the English retranslation and reception of the Spanish classical play La vida es sueño (Calderón de la Barca, 1636). The focus will be on women’s identity in the source text and how it is transmuted in the target plays, particularly emphasising the empowerment and identity granted to female characters. This is most noticeable in the case of Rosaura, who valiantly seeks revenge on Astolfo to restore her honour. To illustrate this, three performance-oriented retranslations staged in the UK and US between 1983 and 2010 will be scrutinised: John Barton and Adrian Mitchell’s Life’s a dream (1983) José Rivera’s Sueño (1998) and Helen Edmundson’s Life is a dream (2009). Together they demonstrate the relevance of non-verbal agency in the process of retranslating women’s identity. Conclusions will highlight the potential of (Spanish) theatre classics as catalysts for gendered retranslations on the Anglophone stage.